Factors Associated with Mothers’ Behaviors in Selecting Complementary Feeding in Surabaya, Indonesia - Pradanie, Retnayu; Rachmawati, Praba Diyan; Cahyani, Meilia Dwi (Nurse Media Journal of Nursing, 2020)
Background: Complementary feeding is usually given to babies at 6 to 24 months of age. Appropriate types, amounts, and methods of complementary feeding are crucial for baby growth and development. Various factors influence mothers’ behavior in selecting complementary feeding.  Purpose: This study aimed to investigate factors affecting mothers’ behaviors in selecting complementary feeding for their babies. Methods: A descriptive analytical study with a cross-sectional approach was conducted on 153 mothers having babies aged 6-12 months old in Surabaya, Indonesia, recruited using simple random sampling. The independent variables were knowledge, attitude, belief, family income, and family support, while the dependent variable was mothers’ behavior in selecting complementary feeding. Data were collected using questionnaires and analyzed using the Spearman rho’s test with a significance level of <0.05.Results: The results showed that knowledge (p=0.021), attitudes (p=0.030), beliefs (p=0.006), income (p=0.000), and family support (p=0.006) were factors affecting mothers’ behavior in selecting complementary feeding.Conclusion: Knowledge, attitudes, beliefs, income and family support had a significant correlation with mothers’ behaviors in selecting complementary feeding. This finding emphasizes pivotal needs to increase knowledge and attitude of complementary feeding for both mothers as the infant primary caregivers, and families as the closest support system for mothers.